The history of endourology in Canada - Beiko, Darren; Honey, R. John D’A.; Pace, Kenneth T.; Denstedt, John D.; Razvi, Hassan; Hosking, Denis H.; Norman, Richard W.; Wilson, James W.L. (Canadian Urological Association Journal, 2019)
Introduction: Following the introduction of shock wave lithotripsy (SWL), ureteroscopy (URS), and percutaneous nephrolithotomy (PCNL), the subspecialty of endourology was born in the late 1970s. The purpose of this study was to report milestones in Canadian endourology, highlighting Canada’s contributions to the field. Methods: A review of the literature was performed from the late 1970s to the present. The literature review included bibliographic and digital resources. Additionally, records and recollections by various individuals were used, including some who were directly involved. Results: Endourology was born in Canada when SWL, URS, and PCNL emerged as minimally invasive treatment options for stones in the early to mid-1980s. According to our research, the first PCNL was performed at the University of Toronto in 1981. Dr. Joachim Burhenne, a Harvard-trained radiologist from Germany, first used extracorporeal SWL in Canada at the University of British Columbia (UBC) for the treatment of biliary stones. Treatment for urinary tract stones followed at UBC and Dalhousie University. The first worldwide use of the holmium laser for lithotripsy of urinary tract calculi took place at the University of Western Ontario. Other endourology milestones in Canada include the formation of the Canadian Endourology Group and the emergence of the Endourological Society-accredited fellowship programs at the University of Toronto and Western University in the 1990s. Canada hosted the 21st and 35th World Congress of Endourology and Shock Wave Lithotripsy annual meeting in Montreal and Vancouver, respectively. Conclusions: Canadian urologists have led many advances in SWL, URS, and PCNL over the past four decades and, for a relatively small community, have made significant contributions to the field. Through the training of the next generation of endourologists at Canadian institutions, the future of endourology in Canada is bright.